Industrial districts in rural areas of Italy and Spain - Rafael Boix; Yancy Vaillant (European Regional Science Association (ERSA), 2010)
The industrial district is a model of production mainly related to medium and small cities characterized by industrial specializations in small and medium enterprises. However, the mapping of the phenomenon in countries as Italy and Spain suggest that industrial districts are also present in rural areas. The objective of this contribution is the identification, mapping and characterization of industrial districts located in rural areas as well as to evaluate the extent in which industrial districts in predominantly rural areas have contributed to the dynamism of these areas. The analysis analyzes the importance of industrial districts for rural development and provides some recommendations regarding policy strategies. Specifically, the study illustrates some relevant results. First, industrial districts are present in rural areas of Italy and Spain although their importance is higher in Spain. Second, industrial districts in rural areas are geographically concentrated in a few rural areas. Third, patterns of specialization of industrial districts in rural areas do not differ from their patterns in other areas. Fourth, predominantly rural areas with industrial districts grow between two and three times faster than the rest of rural areas. Fifth, a significant share of the growth of rural areas with industrial districts is explained by the more dynamic behaviour of these districts. Sixth, the results do not vary when transferring the unit of analysis from industrial districts in rural areas to industrial districts with characteristics of predominantly rural areas. The existence of industrial districts in rural areas and their positive economic impact suggest that they have an important potential for development in those concrete rural areas where they are present. The particularity of industrial districts suggests that any policy strategy including industrial districts should be based on the premises of a flexible bottom up framework where the key governance structure becomes the local level.
Keywords: 330